Russian Federation Customs Development Project : Measurable Progress - Johns, Kimberly; Kristensen, Jens Kromann; McLinden, Gerard (World Bank, Washington, DC, 2012)
The Russian Federation Customs Development Project (CDP), launched in 2003, has been helping reform and modernizes the country's federal customs service. Reforms under the CDP have resulted in improved performance: both customs clearance times and rent-seeking incidents have been reduced. However, despite major progress in critical areas, global rankings such as the world economic forum's enabling trade index and the World Bank's logistics performance index suggest there is still significant room for further improvement in customs administration.